Enhancing Science Process Skills through Process-Oriented Guided Inquiry Learning (POGIL) in Fluid Dynamics - Noor Aulia Azijah; Abdul Salam; Qamariah Qamariah (Universitas Lambung Mangkurat, 2026)
Science Process Skills (SPS) are essential competencies in science learning. However, observations indicate that the SPS of eleventh-grade students at a public high school in Banjarmasin remain relatively low, primarily due to the absence of systematic training in the learning process. Based on the results of a needs analysis, teachers require a learning approach that can effectively facilitate the development of students’ SPS. This study aims to describe the effectiveness of the Process-Oriented Guided Inquiry Learning (POGIL) model in enhancing students’ SPS in the context of fluid dynamics. The research employed a one-group pretest–posttest design. SPS training was implemented through practical activities utilizing both real and virtual laboratories. Data were collected using learning outcome tests (Tes Hasil Belajar/ THB) and SPS observation sheets completed by observers. The data were analyzed quantitatively using descriptive statistics. The results revealed that the n-gain value reached 0.79, indicating a high level of effectiveness, while students’ SPS achievement was classified as very good. These findings demonstrate that the POGIL model is effective in enhancing the SPS of eleventh-grade students in learning fluid dynamics. The implications of this study suggest that the integration of POGIL in physics instruction, particularly in topics that involve experimental and analytical processes such as fluid dynamics, can serve as an effective strategy for developing students’ inquiry skills and readiness for more advanced problem-solving tasks. This model may also provide a framework for teachers to design engaging and skill-oriented learning experiences across other science topics.